A Temperature-Dependent Growth Equation for Larval Chub Mackerel (Scomber japonicus) - Go, Seonggil; Lee, Kyunghwan; Jung, Sukgeun (Ocean science journal, 2020)
Chub mackerel are commercially one of the most important species in the western North Pacific. Variations in water temperature and growth during the early life stages are critical in determining the subsequent recruitment and potential catch of chub mackerel, but yet no study has explicitly provided a temperature-dependent growth equation for chub mackerel larvae. Here we propose a Gompertz-Laird growth equation as a function of ambient water temperature (T) for chub mackerel larvae by revisiting and utilizing the experimental data reported by Hunter and Kimbrell (1980). The derived equation was L t = 38.5126[0.31/38.5126] exp(−αt) , where L t is standard length in cm, t is age in days, and α = 0.0028 exp (0.0971T). Our simulations showed that a difference in the ambient water temperature between 14°C and 25°C can lead to differences in the stage duration of mackerel larvae by a factor of 3, and in the larval survival rate by a factor of 40, suggesting that the variability in temperature-dependent growth can greatly determine the recru i t m e nt success of mackerel. We expect that our derived growth equation will be useful in evaluating and projecting climate-change effects on the recruitment, spatial distribution and potential catch of chub mackerel by developing and applying bio-physical coupling models, but further studies on regional differences regarding growth parameters are required.